PROBLEMS AND PROSPECTS OF ANTIBACTERIAL THERAPY FOR INFILTRATIVE-PURULENT FORMS OF LARYNGITIS IN PEDIATRICS - Shamatov Ислом (International Journal of Scientific Pediatrics, 2025)
Infiltrative-purulent forms of laryngitis in children represent one of the most clinically significant and potentially dangerous pathologies of the upper respiratory tract, characterized by a high risk of acute laryngeal stenosis and purulent-inflammatory complications. In the context of an evolving etiological structure of the disease and the growing prevalence of antibiotic resistance, the selection of optimal antibacterial therapy remains a complex and debated issue. This review systematizes current data on the etiology, pathogenesis, and clinical features of infiltrative-purulent laryngitis in children, and outlines the key principles of rational antibiotic prescribing. Special attention is given to the pathogenetic rationale for the use of various antibiotic classes, their pharmacokinetic properties, and their antimicrobial activity spectrum against common pathogens. The review also addresses issues related to increasing microbial resistance, the frequency of clinical prescribing errors, and insufficient patient compliance. A separate section examines the safety of antibacterial therapy in pediatric practice, including the risks of adverse reactions, age-related limitations, and the need for careful monitoring of potential complications. Furthermore, contemporary approaches to combined treatment are discussed, including the use of systemic glucocorticosteroids, anti-inflammatory agents, inhalation therapy, and surgical interventions in complicated cases. The review highlights key directions for improving antibacterial therapy, such as the development of personalized treatment regimens and the expansion of antibiotic resistance control programs.